ANALISIS PRODUKSI, KONSUMSI DAN PEMASARAN USAHATANI PADI DI DESA LEMBAH ASRI KECAMATAN WEDA SELATAN KABUPATEN HALMAHERA TENGAH - Mahmud, Haris; Sangadji, Suwandi S.; Suhardi, Suhardi (Jurnal Ilmiah Ecosystem, 2021)
The application of rice farming in North Maluku is a response to the record of future agriculture which is increasingly faced with scarce energy resources, the search for and the quality of food, feed, and environmentally friendly energy. The purpose of this study is to provide an overview of the existing agricultural conditions in North Maluku and to formulate steps for the transformation towards rice farming that will be achieved. The condition of rice farming in North Maluku is still at the agronomic level with minimum technology with low productivity indicators (<4 tons / ha), farmer institutions in the beginner class, low group management and semi-subsistence farming orientation. The problems in the application of rice farming consist of technical and non-technical problems so that the application of the agricultural concept must be carried out in stages with the socio-economic and cultural conditions of the community. One of the important factors in producing food is the amount of land because land is the main production factor for producing food. Land is an economic resource whose population is relatively fixed but whose needs continue to increase due to development needs. In addition, land also has specific characteristics (topography, slope, soil texture, chemical content.)